Cycling attributes that enhance running performance after the cycle section in triathlon - Etxebarria, N.; Anson, J. M.; Pyne, D. B.; Ferguson, R. A. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To determine how cycling with a variable (triathlon-specific) power distribution affects subsequent running performance and quantify relationships between an individual cycling power profile and running ability after cycling. Methods: Twelve well-trained male triathletes (VO2peak 4.9 ± 0.5 L/min; mass 73.5 ± 7.7 kg; mean ± SD) undertook a cycle VO2peak and maximal aerobic power (MAP) test and a power profile involving 6 maximal efforts (6 s to 10 min). Each subject then performed 2 experimental 1-h cycle trials, both at a mean power of 65% MAP, at either variable power (VAR) ranging from 40% to 140% MAP or constant power (CON) followed by an outdoor 9.3-km time-trial run. Subjects also completed a control 9.3-km run with no preceding exercise. Results: The 9.3-km run time was 42 ± 37 s slower (mean ± 90% confidence limits [CL]) after VAR (35:32 ± 3:18 min:s, mean ± SD) compared with CON cycling (34:50 ± 2:49 min:s). This decrement after VAR appeared primarily in the first half of the run (35 ± 20 s; mean ± 90% CL). Higher blood lactate and rating of perceived exertion after 1 h VAR cycling were moderately correlated (r = .51-.55; ± ~.40) with a larger decrement in run performance. There were no clear associations between the power-profile test and decrement in run time after VAR compared with CON. Conclusions: A highly variable power distribution in cycling is likely to impair 10-km triathlon run performance. Training to lower physiological and perceptual responses during cycling should limit the negative effects on triathlon running.